Revealing cryptic diversity and population divergence in subtropical aphids through DNA barcoding - Li, Qiang; Liu, Qian; Yu, Yuhua; Lin, Xiaolan; He, Xueyou; Huang, Xiaolei (Zoologica scripta, 2023)
Aphids are worldwide distributed pests, which feed on plant sap and cause serious losses to agricultural and forestry industries. Relatively few comprehensive studies have been conducted on aphid diversity in subtropics, although these regions may harbour hidden aphid diversity due to high plant diversity. In this study, we conducted DNA barcoding analysis for aphids in subtropical regions based on a comprehensive DNA barcode reference library including 5821 sequences and related ecological information (e.g. geography, host plant) of 379 morphospecies. In the reference library, 2140 sequences and related data of 151 morphospecies belonging to 77 genera and 11 subfamilies were newly produced by the current study. The average Kimura 2‐parameter distances within species, genera and subfamilies were 0.92%, 3.55% and 8.3%, respectively. The minimum interspecific distances were greater than the maximum intraspecific distances in 79.8% species, suggesting that barcode gaps existed in most aphid species. Automatic barcode gap discovery, Barcode Index Number, Bayesian Poisson tree processes and generalized mixed Yule‐coalescent revealed 419, 401, 462 and 455 single species‐representing clusters, respectively. A total of 32 morphospecies were assigned to more than one subclade respectively, suggesting geography or host plant‐mediated divergences and the existence of cryptic diversity. This study demonstrates that subtropical regions should have a higher species diversity of aphids, and cryptic species in certain morphospecies indicated in this study need to be investigated based on integrative taxonomic practices in the future. The DNA barcode reference library constructed herein provides a robust baseline data set to support future research in taxonomy, phylogenetics, ecology and evolution of aphids.